Correlations between theoretical calculations and experimental photochemical reactivity of hydroxyanthraquinone drugs present in Aloe vera - Ruette, Fernando; Vargas, Franklin; Rivas, Lourdes (Ciencia)
The phototoxic drugs (S) (aloe-emodin (1), emodin (2), and rhein (3)) were studied with the parametric method CATIVIC in order to find correlations between calculated theoretical properties and the experimental photodegradation rate. These correlations can be explained through the formation of free radical intermediates, singlet oxygen and stable photoproducts. A correspondence between calculated dipolar moment and heat of formation with photolysis rate and quantum yield (_fl) of anthraquinones (1, 2 and 3) was found. In addition,HOMOenergy correlates with the wavelength of excitation (exc). Formation of S-, SH°, and 1O2 intermediates were evaluated and confirmed as feasible. The O2 - anion is found to be the most probable species in the photooxidation of biological substrates